Relationship of the Physical Environment with the Incidence of ARI in Toddlers - Titi Saparina L; Rasni Intan (Universitas Mandala Waluya, 2021)
Factors that are closely related to the occurrence of ARI is the physical environment that does not meet health requirements. The group that has a high risk of being exposed to Acute Respiratory Infection (ARI) is toddlers as a vulnerable group because they have more time at home and their immune system is quite weak than adults. This study is aim to at studying the correlation between physical environment with the incidence of ARI toddlers in Kandai Health Center Area, Kendari City. This type of study is analytic with a Cross-Sectional Study plan. The study population was 1.576 people and the sample was 94, using Accidental Sampling. Data testing utilizes the Chi-Square test. Chi-Square test results obtained ventilation (p-value=0.001 and phi value=0.359), population density (p-value=0.002 and phi value=0.348), smoke holes (p-value=0.025 and phi value=0.255), floor types (p-value=0.040 and phi value=0.236) and wall types (p-value=0.012 and phi value=0.282). It means that there is a correlation between ventilation area, population density, smoke holes, wall type and floor type with the occurrence of ARI in toddlers in the Kandai Health Center area, Kendari City. It is expected that the relevant health agencies to play a more role in increasing public knowledge through counseling to reduce the number of cases of ARI disease in toddlers.